Assessment matrix of the touristic potential of receptive locations - Almeida, Marcelo Vilela de (Revista Turismo em Análise, 2009)
This paper proposes an assessment matrix of tourism development potential for receptive locations based on: an exploratory literature review; definition of the focus of the study (Guaratinguetá and Cunha, both located in the state of São Paulo); bibliographical and field research on these cities; elaboration, development and application of the matrix to both cities, data analysis, comparison and discussion in the light of the theoretical framework. Finally, Guaratinguetá and Cunha's tourism development potential is evaluated according to the definition proposed. It is then suggested the application of this assessment matrix to other cities.